PSYCHO-SOCIAL FACTORS CONTRIBUTING TO SUPERSTITIOUS BEHAVIOR: LITERATURE REVIEW - Shrivastav, Manasvi; Kotnala, Anuradha (International Journal of Research -GRANTHAALAYAH, 2015)
Most superstition from the past have been proven by science as unnecessary, ineffective or just plain silly but are still practiced by normal intelligent people today. Around the world, there are many reappearing themes for superstition. Every country has its own localized take on each theme. In this article researcher reviews on previous researches. There is much different kind of researches in the field of superstition and there are different theories related to the origin of superstition. Superstition is influenced by different social and psychological factors. In this article those researches have been discussed which through light on social and psychological factors of superstition. Psychological factors like fear, locus of control, confidence level etc. and social factors such as locale, socio-economic status etc.